Analysis of expressed sequence tags (ESTs) from avocado seed (Persea americana var. drymifolia) reveals abundant expression of the gene encoding the antimicrobial peptide snakin - Guzmán-Rodríguez, Jaquelina J (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.